Effect of chromium variation on evolution of magnetic properties in laser direct energy additively processed CoCrxFeNi alloys. (15th March 2023) - Radhakrishnan, M.; McKinstry, M.; Chaudhary, V.; Nartu, M.S.K.K.Y.; Krishna, K.V. Mani; Ramanujan, R.V.; Banerjee, R.; Dahotre, Narendra B.
Abstract: The soft magnetic behavior of laser directed energy deposited CoCrx FeNi ( x = 0 - 24 at.% Cr) alloys has been investigated as a function of chromium content. The saturation magnetization of these CoCrx FeNi alloys monotonically decreased with increasing concentration of Cr, and exhibited paramagnetic behavior at room temperature for equiatomic CoCrFeNi alloy composition. Similarly, the Curie temperature (Tc ) of the ferromagnetic CoFeNi alloy linearly decreased with Cr content, while the paramagnetic equiatomic alloy indicated a ferromagnetic transition temperature of 94 K. Interestingly, all the as-deposited alloys exhibited coercivity values less than 2 Oe irrespective of the Cr content. The results indicate that the magnetic behavior of the ferromagnetic CoFeNi alloy can be systematically tuned with addition of antiferromagnetic Cr, and the additive manufacturing route was successful in rapid processing alloys of any desired composition, in a high throughput manner, with negligible chemical variation. These findings are promising for the fabrication of components for applications demanding gradient magnetic coatings and alloys. Graphical abstract: Image, graphical abstract